Analysis of Implementation of Elementary School Teachers Competence in Sungai Raya - Maha Lastasabuju Basafpipana Habaridota (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
This study aims to determine the analysis of the implementation of the competence of public elementary school teachers in Sungai Raya subdistrict, Kubu Regency. The study was conducted in Sungai Raya Subdistrict with 29 elementary school teachers. Data collected are pedagogical, personal, social, and professional competencies using data collection tools in the form of interview sheets, non-participant observation sheets, and documentation. Data analysis uses a checklist matrix technique with several stages, namely: data collection, data reduction, data display, drawing conclusions. The results showed that: First, the implementation of pedagogical competencies by public elementary school teachers in Sungai Raya Subdistrict, Kubu Raya District, was interpreted that the teacher's ability to educate reached an average of 3.37 with a good category. Second, the personality competency of public elementary school teachers in Sungai Raya Subdistrict, Kubu Raya Regency, averaged 3.30 in the good category. Third, the social competency of public elementary school teachers in Sungai Raya District is an average of 3.37 with a good category. The four professional competencies of public elementary school teachers in Sungai Raya District reach an average of 3.30 in the good category. The results of this study, it is suggested to be a reference for similar research related to teacher competencies, which should be part of the teacher to dedicate himself to serve especially elementary school teachers in Sungai Raya District Kubu Raya District.